1991
DOI: 10.1111/j.1365-2125.1991.tb03952.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of octreotide (SMS 201‐995) on diabetic ketogenesis during insulin withdrawal.

Abstract: 835 ,umol 1-1 h, AUC, P = NS) were not significant, but the peak increments of acetoacetate (1413 ± 354 ,umol F-1 vs 612 ± 176 ,mol F-1, P < 0.05), ,3-hydroxybutyrate (2180 ± 475 ,umol 1-1 vs 922 ± 246 ,umol 1-1, P < 0.01) and the decrements in plasma bicarbonate (-8 ± 1 ,umol F-1 vs -4 ± 1 ,umol F-1, P < 0.05) and pH (-0.07 + 0.01 vs -0.03 ± 0.01, P < 0.05) were significantly less with octreotide. 4 At the same time peak increments of glucagon were lower with octreotide treatment (329 ± 206 pg ml-' vs 39 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition, approximately 28%–65% of instances of DKA occurred in young T1DM patients due to omitted insulin injections; therefore, omitting insulin injection is the major cause of DKA in children and young adults with T1DM [13] , [21] , [22] , [23] , [24] , [25] . In patients with T1DM, after 4–6 h of withdrawal from insulin administration ketone bodies will increase, which eventually increases the risk of DKA [26] , [27] .After premixed insulin injection, serum insulin concentration may reach its maximum level 60–100 min after injection and down to relatively low level after around 15–18 h [28] , [29] , [30] , [31] . If patients miss one dose of premixed insulin injection, it means not only losing one-third to one-half of the total daily insulin dose, but also means exposing the patient in a relative or absolute insulin deficiency period, which would increase the risk of DKA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, approximately 28%–65% of instances of DKA occurred in young T1DM patients due to omitted insulin injections; therefore, omitting insulin injection is the major cause of DKA in children and young adults with T1DM [13] , [21] , [22] , [23] , [24] , [25] . In patients with T1DM, after 4–6 h of withdrawal from insulin administration ketone bodies will increase, which eventually increases the risk of DKA [26] , [27] .After premixed insulin injection, serum insulin concentration may reach its maximum level 60–100 min after injection and down to relatively low level after around 15–18 h [28] , [29] , [30] , [31] . If patients miss one dose of premixed insulin injection, it means not only losing one-third to one-half of the total daily insulin dose, but also means exposing the patient in a relative or absolute insulin deficiency period, which would increase the risk of DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Diem et al were assessed preventive effects of octreotide on diabetic ketogenesis during insulin withdrawal. Octreotide led to a marked suppression of beta-hydroxybutyrate, acetoacetate and glucagon levels and an associated diminution of bicarbonate consumption and the fall in pH [190]. Anthony et al reported a case of DKA with glucagonoma who was unresponsive to conventional therapy and treated with octreotide [191].…”
Section: Somatostatin Therapy In the Management Of Resistant Diabeticmentioning
confidence: 99%
“…Circulating levels of CRHs including glucagon, growth hormone, cortisol and catecholamines are higher in patients with DKA compared to HHS, and administration of cortisol, glucagon and catecholamines to patients with type 1 diabetes results in ketosis. The causative role of CRH excess in DKA is convincingly demonstrated by studies utilising somatostatin and its analogue octreotide to mediate glucagon suppression, with administration to insulin‐deprived patients with type 1 diabetes resulting in profound suppression of ketogenesis and a less significant effect on hyperglycaemia . Finally, CRH suppression with beta‐blockers and somatostatin has shown relevance in the prevention and treatment of DKA.…”
Section: Introductionmentioning
confidence: 99%